2016
DOI: 10.3923/rjet.2016.82.87
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metal Levels in Some Commonly Consumed Frozen Fish in Ibadan, Southwest, Nigeria

Abstract: There is a growing concern on the safety of frozen fish imported from various parts of the world where the levels of contamination of water bodies may not be well ascertained and regulatory measures not strictly adhered to. Concentrations of four heavy metals (Lead (Pb), Cadmium (Cd), Copper (Cu) and Mercury (Hg)) in the muscle, gill and liver were investigated for three most consumed frozen fish species (Umbrina canosai, Clupea harengu and Scomber scombrus) within Ibadan, metropolis. Samples were digested as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
(15 reference statements)
0
10
6
Order By: Relevance
“…However, the Pb level in this study was higher than those reported by Jenyo-Oni and Oladele (2016) in Oreochromis niloticus. On the contrary, Pb content in the present study was lower than those recorded in Scomber scombrus by Abubakar et al, (2014) and Kareem et al, (2016). The presence of heavy metals in the fish samples is an indication that the fish is exposed to pollution whose sources could be either point or non-point sources.…”
Section: Resultscontrasting
confidence: 81%
“…However, the Pb level in this study was higher than those reported by Jenyo-Oni and Oladele (2016) in Oreochromis niloticus. On the contrary, Pb content in the present study was lower than those recorded in Scomber scombrus by Abubakar et al, (2014) and Kareem et al, (2016). The presence of heavy metals in the fish samples is an indication that the fish is exposed to pollution whose sources could be either point or non-point sources.…”
Section: Resultscontrasting
confidence: 81%
“…The Zn, Pb and Cd values in fish in this study are above those found in Oreochromis niloticus [11] and in Pseudotolithus elongatus [32]. On the contrary, Pb and Cd contents recorded in C. nigrodigitatus in the present study is lower than the valus recorded in Scomber scombrus [34,35]. The results of this study is comparable to earlier reports on fish samples from Anambra River [36], Calabar River [37] and Izmir bay in Turkey [38].…”
Section: Heavy Metals In Sediment Plant and Fish Speciescontrasting
confidence: 73%
“…Olusola and Festus [79] during their study of coastal waters of Ondo state, noted that distribution of heavy metals in different fish parts were organ specific, Heavy Metals -Their Environmental Impacts and Mitigation as higher concentrations of metals were recorded in the gills and eyes compared to other organs. In contrast, [80] recorded highest concentration of Pd, Cd, Cu and Hg in liver than other parts of frozen fishes sold in storage facilities in Ibadan, Oyo State. Some of the concentrations recorded in these parts were considered to be above maximum acceptable limit by [81].…”
Section: Heavy Metals Toxicity In Freshwater Fishesmentioning
confidence: 75%